From large-scale environment to CGM angular momentum to star-forming activities – I. Star-forming galaxies. Issue 3 (2nd November 2021) - Wang, Sen; Xu, Dandan; Lu, Shengdong; Cai, Zheng; Xiang, Maosheng; Mao, Shude; Springel, Volker; Hernquist, Lars
ABSTRACT: The connection between halo gas acquisition through the circumgalactic medium and galaxy star formation (SF) has long been studied. In this series of two papers, we put this interplay within the context of the galaxy environment on large scales (several hundreds of kpc), which, to a certain degree, maps out various paths for galaxy interactions. We use the IllustrisTNG-100 simulation to demonstrate that the large-scale environment modulates the circumgalactic gas angular momentum, resulting in either enhanced (Paper I) or suppressed (Paper II) SF inside a galaxy. In this paper (Paper I), we show that the large-scale environment around a star-forming galaxy is often responsible for triggering new episodes of SF. Such an episodic SF pattern is well synced with a pulsating motion of the circumgalactic gas, which, on the one hand, receives angular momentum modulations from the large-scale environment, yielding in-spiralling gas to fuel the star-forming reservoir, while, on the other hand, is affected by the feedback activities from the galaxy centre. As a result, a present-day star-forming galaxy may have gone through several cycles of star-forming and quiescent phases during its evolutionary history, with the circumgalactic gas carrying out a synchronized cadence of 'breathing in and out' motions out to ∼100 kpc.